Heterogeneity Within Youth With Childhood-Onset Conduct Disorder in the ABCD Study - Brislin, Sarah J.; Martz, Meghan E.; Cope, Lora M.; Hardee, Jillian E.; Weigard, Alexander; Heitzeg, Mary M. (Frontiers in Psychiatry, 2021)
The purpose of this study was to examine if personality traits can be used to characterize subgroups of youth diagnosed with childhood-onset conduct disorder (CD). Participants were 11,552 youth from the Adolescent Brain Cognitive Development study. Data used in this report came from DOI: 10.15154/1504041 (M age 9.92; 45.3% female, 49.6% white, 19.0% Hispanic). A subset of this sample (n = 365) met criteria for CD. Latent profile analyses (LPA) were performed on this subgroup (n = 365) to define profiles of individuals with CD based on self-report measures of impulsivity, punishment sensitivity, reward response, and callous-unemotional traits. Follow up analyses determined if these groups differed on clinically relevant variables including psychopathology, environmental risk factors, social risk factors, and neurocognitive functioning. Participants with a CD diagnosis scored significantly higher on psychological, environmental, social, and neurocognitive risk factors. The LPA revealed three unique profiles, which differed significantly on liability for broad psychopathology and domain-specific liability for externalizing psychopathology but were largely matched on environmental and social risk factors. These unique configurations provide a useful way to further parse clinically relevant subgroups within youth who meet criteria for childhood-onset CD, setting the stage for prospective longitudinal research using these latent profiles to better understand the development of youth with childhood-onset CD.